Knowledge and Practice for Bio-Medical Waste Management among Healthcare Personnel at Kabgayi District Hospital, Rwanda - Erigene, Rutayisire; Jean, Aime Nsabimana; Michael, Habtu (Journal of Public Health International, 2019)
Background Globally, about 10 to 25% of the volume of bio-medical waste from hospitals and healthcare institutions presents a serious health risks to patients, healthcare personnel, and anybody who comes in contact with it. The waste management practices in Rwanda healthcare facilities are poor and need improvement. Objectives To assess the knowledge and practices regarding bio-medical waste management among healthcare personnel at Kabgayi district hospital in Southern Province of Rwanda. Materials and Methods A cross-sectional study design was conducted. A total of 200 healthcare personnel were selected randomly out of 400 target population including doctors, nurses, social workers, and cleaners. Structured questionnaire was used to collect data. Descriptive analysis using frequency and proportions were used. Chi-Square test was used to determine the association between the variables and level of significance was set at p ≤ 0.05. Results The study found that about half (49.0%) of healthcare personnel had good knowledge about waste management. We found that the majority of healthcare personel 133(66.5%) had poor practices towards bio-medical waste management. The factors associated with good practice were better knowledge on bio-medical waste management (p=0.013) and older age group (p=0.001). Conclusion/Recommendations The level of in both knowledge and practice towards bio-medical waste management among healthcare personnel was low. Continuing education and training programmes and short courses on bio-medical waste management should be carried out to improve the knowledge and practices towards bio-medical waste management among healthcare personnel.
Keywords: Bio-Medical Waste Management; Rwanda Healthcare Facilities; Healthcare Personnel; Knowledge; Practice